3D-imaging of boulders using a solid-state 2D profilometer: case study for autonomous robotic rock breaker. (19th June 2023) - Niskanen, Ilpo; Lampinen, Santeri; Immonen, Matti; Hallman, Lauri; Mikkonen, Martti; Karvinen, Jarno; Kostamovaara, Juha; Mattila, Jouni; Heikkilä, Rauno
Measurements of a boulder's fundamental physical properties like volume and shape can offer valuable insights for secondary breaking of boulders by a robotic rock breaker. This study analysed boulder shapes using a pulsed time-of-flight (TOF) solid-state laser profilometer. The 3D surface of boulders was reconstructed creating triangular meshes from point clouds provided by the profilometer. The main advantages of the 2D profilometer are the good measurement precision and accuracy, high speed, small size, real-time measurement capability, low weight, eye-safety, and lack of moving parts. The results indicate that a 3D map facilitates boulder diagnostics, aids in decision making, and represents a step towards a fully integrated autonomous robotic rock breaker in the mining industry. The present procedure is not only restricted to boulders, but it has also potential for other targets in industries that require precise determination of shapes for decision making.